Respuesta :

Answer:

None of these answers are correct but if you meant 3x²-8x+5 then the answer would be D. (3x – 5)(x - 1)

Step-by-step explanation:

3 x 2 - 8x + 5 = 6 - 8x+5

6 - 8x + 5 = 11 - 8x

A. (3x - 1)(x + 5)  = 3x²-1x+15x-5 = 3x²+14x-5

B. (3x + 5)(x - 1)  = 3x²-3x+5x-5 = 3x²+2x-5

C. (3x – 1)(– 5)  = -15x-5

D. (3x – 5)(x - 1) = 3x²-3x-5x+5 = 3x²-8x+5

So none of these answers are correct but if you meant 3x²-8x+5 then the answer would be D. (3x – 5)(x - 1)

Answer:

D.) (3x-5)(x-1)

Step-by-step explanation: